Edukasi Komunitas SIBAT Berbasis Memori Kolektif Ekologis dalam Mitigasi Bencana Banjir di Kampung Sewu, Surakarta - Hasliza Tartila Maulida; Erisfa Fathimatuz Zahro; Hasan Ashari (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Floods are a frequent occurrence in Surakarta City, especially in Kampung Sewu Village. Disaster mitigation education efforts must be continuously conducted to anticipate higher risks. This study aims to determine how flood mitigation education conducted by SIBAT is based on the community's collective ecological memory. This research is a qualitative study with a case study approach. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis techniques used the Miles & Huberman interactive analysis model which consists of three stages: data reduction, data presentation, and conclusion drawing and verification. Based on the results of the study, it can be concluded that: SIBAT was born from the collective ecological memory of the Kampung Sewu community formed through long experience facing flood disasters, then transformed into a mitigation education forum that includes training in preparedness, environmental management, food security, and dissemination of disaster information.